1992
DOI: 10.1073/pnas.89.18.8832
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and structure of a DNA tetraplex: a spectroscopic and calorimetric study of the tetramolecular complexes of d(TG3T) and d(TG3T2G3T).

Abstract: We report a combined thermodynamic and structural characterization of a DNA tetraplex. Using spectroscopic and calorimetric techniques, we demonstrate that d(TG3T) and d(TG3T2G3T), in the presence of K+, form stable tetramolecular complexes. From differential anning calorimetry measurements, we obtain the following thermodynamic profiles for formation of each tetraplex at 25C: AG' = -6.9 kcal/mol oftetraplex (or -2.3 kcal/mol of tetrad; 1 cal = 4.184 X), AH0 = -62.6 kcal/mol of tetraplex (or -20.9 kcal/mol of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
129
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(145 citation statements)
references
References 47 publications
16
129
0
Order By: Relevance
“…Telomeric and nontelomeric G-rich sequences can form G4-DNA structures [reviewed by Sundquist (1991), Henderson et al (1987), Williamson et al (1989), Sundquist and Klug (1989), Sen and Gilbert (1990), Jin et al (1992), Kang et al (1992), and Smith and Feigon (1992)l. This study demonstrates that Tetrahymenacontains an abundant protein, TGP, that binds specifically to G4 structures formed by the telomeric G-strand sequence d(TzG4)4 and not to Tet 4 intramolecular foldback monomers or to unstructured Tet 4 monomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomeric and nontelomeric G-rich sequences can form G4-DNA structures [reviewed by Sundquist (1991), Henderson et al (1987), Williamson et al (1989), Sundquist and Klug (1989), Sen and Gilbert (1990), Jin et al (1992), Kang et al (1992), and Smith and Feigon (1992)l. This study demonstrates that Tetrahymenacontains an abundant protein, TGP, that binds specifically to G4 structures formed by the telomeric G-strand sequence d(TzG4)4 and not to Tet 4 intramolecular foldback monomers or to unstructured Tet 4 monomers.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic oligonucleotides containing telomeric G-strand sequences are able to form unusual structures mediated by cyclic hydrogen-bonded arrays of guanines (G-quartets) [reviewed by Sundquist (1991), Williamson et al (1989), Sundquist and Klug (1989), Kang et al (1992), and Smith and Feigon (1992)l. These structures include antiparallel, intramolecular quadruplex (G'2-DNA) (Henderson et al, 1987;Williamson et al, 1989;Sen & Gilbert, 1990;Jin et al, 1990;Kang et al, 1992) and parallel-stranded intermolecular quadruplex (G4-DNA) structures (Zimmerman et al, 1975;Sen & Gilbert, 1990;Jin et al, 1992;Aboul-ela et al, 1992;Gupta et al, 1993). Intramolecular G-DNA structures migrate faster than linear forms of the same length in nondenaturing gels (Henderson et al, 1987;Williamson et al, 1989) while intermolecular structures migrate more slowly (Sen & Gilbert, 1990;Acevedo et al, 1991;Sundquist & Klug, 1989).…”
mentioning
confidence: 99%
“…For selection, we used the biotinylated Stylonychia telomeric sequence, denoted b-sty (5Ј-TTTTTGGGGTTTTGGGGTTTTGGGGTTTTGGGG-3Ј), in the parallel quadruplex conformation. Parallel and antiparallel quadruplex structures of the sequences examined were prepared as described (11,22) and further purified to conformational homogeneity by gel filtration with a Superdex-75 column (Amersham Pharmacia). All DNA conformations were confirmed by CD spectroscopy using a Jasco 715 spectropolarimeter (11,23).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the G-rich overhang can adopt a variety of unusual DNA structures (4), of which guanine-quadruplex DNA and t-loops are stable in vitro under physiological conditions (5)(6)(7)(8). Parallel-stranded as well as antiparallel-stranded guaninequadruplex structures have been biophysically and structurally analyzed in detail with synthetic oligonucleotides (6)(7)(8)(9)(10)(11). It has been suggested that this structure is also involved in numerous cellular processes, including transcription and recombination, in addition to telomere function (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation